2017
DOI: 10.1039/c7dt01950e
|View full text |Cite
|
Sign up to set email alerts
|

Facile activation of alkynes with a boraguanidinato-stabilized germylene: a combined experimental and theoretical study

Abstract: A boraguanidinato-stabilized germylene, [(i-Pr)NB(N-2,6-MeCH)]Ge, reacts with alkynes RC[triple bond, length as m-dash]CR selectively in a 2 : 1 molar ratio to afford 3,4-R,R'-1,2-digermacyclobut-3-enes 1a-e as the products of formal [2 + 2 + 2] cyclization [R/R' = Me/Me (1a), Ph/Ph (1b), Ph/H (1c), t-Bu/H (1d) and Cy/H (1e)]. Ferrocenyl-substituted alkynes react similarly, yielding the corresponding ferrocenylated 3,4-R,R'-1,2-digermacyclobut-3-enes 2a-d [where R/R' = Fc/H (2a), Fc/Me (2b), Fc/Ph (2c), and Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 114 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…The treatment of germylene 1 with above mentioned alkynes resulted in a smooth [2+2+2] cyclization and formation of the respective 3‐Fc‐4‐C(O) R ‐1,2‐digermacyclobut‐3‐enes 2 – 4 [ R = Me ( 2 ), OEt ( 3 ), and NMe 2 ( 4 )] (Scheme ). No products resulting from an attack of the germylene on the carbonyl moiety could be isolated and the reactivity of 1 thus resembles that described earlier for simple alkynes …”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The treatment of germylene 1 with above mentioned alkynes resulted in a smooth [2+2+2] cyclization and formation of the respective 3‐Fc‐4‐C(O) R ‐1,2‐digermacyclobut‐3‐enes 2 – 4 [ R = Me ( 2 ), OEt ( 3 ), and NMe 2 ( 4 )] (Scheme ). No products resulting from an attack of the germylene on the carbonyl moiety could be isolated and the reactivity of 1 thus resembles that described earlier for simple alkynes …”
Section: Resultssupporting
confidence: 71%
“…Molecular structures determined by single‐crystal X‐ray diffraction analysis revealed that the central 1,2‐digermacyclobut‐3‐ene cores of 3 and 4 (Figure and Figure ) are structurally similar to those found in 3‐Fc‐4‐ R ‐1,2‐digermacyclobut‐3‐enes ( R = H or Ph). These rings comprise C=C double bond [1.334(10) in 3 , and 1.345(12) Å in 4 , cf.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition to constituting an interesting class of new transition metal ligands, 10 15 several of these compounds are able to participate in small molecule bond activation reactions. 16 19 …”
Section: Introductionmentioning
confidence: 99%